2011
DOI: 10.1253/circj.cj-10-0918
|View full text |Cite
|
Sign up to set email alerts
|

The Follow-up Evaluation of Electrocardiogram and Arrhythmias in Children With Fluminant Myocarditis

Abstract: Background: Fulminant myocarditis involves various serious arrhythmias that sometimes have lethal consequences. The purpose of the present study was to investigate the electrocardiogram findings, arrhythmogenicity and abnormalities of the cardiac conduction system in children with fulminant myocarditis. Methods and Results:Between 1999 and 2008, 7 consecutive patients (mean age: 7 years) who suffered from fulminant myocarditis were included in the study. A 12-lead electrocardiogram, Holter monitoring and signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 18 publications
0
31
0
4
Order By: Relevance
“…Premature contractions and a wide variety of tachyarrhythmias and bradyarrhythmias occur in myocarditis, including complete atrioventricular block. 28,29 …”
Section: Electrocardiographymentioning
confidence: 99%
“…Premature contractions and a wide variety of tachyarrhythmias and bradyarrhythmias occur in myocarditis, including complete atrioventricular block. 28,29 …”
Section: Electrocardiographymentioning
confidence: 99%
“…19 Echocardiography often shows globally, or sometimes segmentally, reduced wall motion, a mildly dilated ventricular cavity with or without wall thickening, atrioventricular valve regurgitation, wall motion abnormalities, and pleural effusion. Transient ventricular wall thickening is rarely observed on echocardiography in children with acute MC, 20 and is reported to be caused by interstitial edema, as indicated in a comparison of the pathological findings of biopsy specimens from patients in the acute or convalescent phase.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…In fact, heart failure due to myocarditis or dilated cardiomyopathy itself increased the vulnerability of the patients to tachyarrhythmia and conduction disturbance 24). Ichikawa et al25) reported that 3 of 7 patients with fulminant myocarditis developed ventricular tachycardia or ventricular fibrillation. Friedman et al26) also documented the high incidence rate of arrhythmia in pediatric idiopathic dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%